2007
DOI: 10.1002/ptr.2322
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on hypotensive, diuretic and vasodilator activities of chrysin glucoside from Calycotome villosa in rats

Abstract: The present study was undertaken in normotensive anaesthetized male rats that received a continuous perfusion of a chrysin glucoside isolated from the flowers and leaves of Calycotome villosa subsp intermedia at a dose of 2.5 mg/kg, or furosemide (control diuretic) at a dose of 0.5 mg/kg. Compared with the control rats receiving NaCl (0.9%), the urine flow, glomerular filtration and electrolyte excretion (Na+, K+) increased significantly in rats treated with chrysin glucoside (p < 0.001). A similar effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Intermedia [ 3 ] but this is the first time it has been isolated from this species. Previous studies showed hypotensive and diuretic properties of this compound and they revealed an ability to increase the α-transcriptional activity in MCF-7 cells [ 42 , 43 ]. In our work, a weak antioxidant activity toward the radical DPPH .…”
Section: Discussionmentioning
confidence: 99%
“…Intermedia [ 3 ] but this is the first time it has been isolated from this species. Previous studies showed hypotensive and diuretic properties of this compound and they revealed an ability to increase the α-transcriptional activity in MCF-7 cells [ 42 , 43 ]. In our work, a weak antioxidant activity toward the radical DPPH .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alkaloids have also been found to exhibit a vasoconstrictive 42 effect mediated through the release of Ca +243 and through endotheliumdependent pathway. 44 Glucosides and sesquiterpenes 45 are also known to possess an inhibitory effect on cardiovascular system. The current findings on the cardiovascular activities of Acorus calamus can be possibly correlated to its chemical constituents, particularly alkaloids in addition to glucosides and sesquiterpenes, which might be responsible for the antihypertensive and vasomodulatory effects because the other chemical constituents such as acorine and asarone are not known to possess effects related to the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…1), is known for its various biological activities (6,7). Previous studies have suggested that chrysin possesses antioxidant (8), antihypertensive (9), antidiabetogenic (10) and anxiolytic properties (11). In addition, chrysin exerts a strong anticancer effect in multiple types of human cancer, since it induces cell cycle arrest and cell apoptosis (12); however, whether chrysin may be used as a novel antitumor drug against HCC has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%